Evaluation of Village Empowerment Funds in Kelurahan Kawangu, Sumba Timur - Lusianus Heronimus Sinyo Kelen; Raynesta M. I. Malo; Diana A. Djoh (LP2M Universitas Jember, 2021)
Community empowerment funds that are managed at both the village and sub-district levels are an important aspect of community empowerment and development. East Sumba Regency certainly has a number of government programs to give funding to the community at the village and sub-district levels. However, it is difficult to control and evaluate the funding due to limited knowledge and skills. Through the program of KKN-PPM held by Universitas Kristen Wira Wacana Sumba in Kawangu Village, East Sumba Regency, an evaluation program for community empowerment funds was held. Several parties participated in this program were lecturers, students, village government officials, and the beneficiaries. This evaluation, which was carried out from 21 August to 14 September 2020, included four types of businesses, fisheries and marine business, agricultural product business, weaving business, and machine shop services. The results of this evaluation will certainly help the Government of Kawangu in determining policies related to empowerment in the future.